The Effect Of Surface Recombination On The Frequency-Dependent Characteristics Of An Ion-Implanted Gaas Opfet - Mishra S.; Singh V.K.; Pal B.B. (My University, 2025)
The effect of modulation frequency and surface recombination on the characteristics of an ion-implanted GaAs OPFET is carried out analytically. The drain-source current is found to decrease with the increase in both modulation frequency and trap center density. The current changes significantly with the trap center density only when it is greater than 1020/m2. The threshold voltage does not change appreciably with the modulation frequency as in silicon Opfet. How-ever, the increase in the trap center density increases VT in the enhancement device and decreases in the depletion device. Further, VT, is found to be increased under normally ON condition and decreased under normally OFF condition with the increase in the photon absorption coefficient in GaAs. Some anomaly is observed for higher values of the absorption coefficient. © 1990 IEEE